Enhanced biodegradation of 2, 4-dichlorophenol in packed bed biofilm reactor by impregnation of polyurethane foam with Fe3O4 nanoparticles: Bio-kinetics, process optimization, performance evaluation and toxicity assessment - Kumar Jaiswal V.; Dutta Gupta A.; Sonwani R.K.; Shekher Giri B.; Sharan Singh R. (My University, 2025)
In this work, an effort has been made to enhance the efficacy of biological process for the effective degradation of 2, 4-dichlorophenol (2, 4-DCP) from wastewater. The polyurethane foam was modified with Fe3O4 nanoparticles and combined with polyvinyl alcohol, sodium alginate, and bacterial consortium for biodegradation of 2, 4-DCP in a packed bed biofilm reactor. The maximum removal efficiency of 2, 4-DCP chemical oxygen demand, and total organic carbon were found to be 92.51 ± 0.83 %, 86.85 ± 1.32, and 91.78 ± 1.24 %, respectively, in 4 days and 100 mg L−1 of 2, 4-DCP concentration at an influent loading rate of 2 mg L−1h−1 and hydraulic retention time of 50 h. Packed bed biofilm reactor was effective for up to four cycles to remove 2, 4-DCP. Growth inhibition kinetics were evaluated using the Edward model, yielding maximum growth rate of 0.45 day−1, inhibition constant of 110.6 mg L−1, and saturation constant of 62.3 mg L−1. © 2024 Elsevier Ltd